A new class of quantile functions useful in reliability analysis. (3rd July 2018) - Sankaran, Paduthol Godan; Kumar M, Dileep
ABSTRACT: This article introduces a new flexible family of distributions, defined by means of a quantile function. The quantile function proposed is the sum of quantile functions of the half logistic and exponential geometric distributions. Various distributional properties and reliability characteristics are discussed. The estimation of the parameters of the model using L-moments is studied. The model is applied to a real-life data set.